Protective Effects of Ethanol Extract of Chrysophyllum albidum Stem Bark on Antioxidant Enzymes and Lipid Peroxidation Induced Kidney Toxicity in Albino Rats Exposed to Bonny Light Crude Oil - Jemimah Hebrew; Markus Audu; Isaac John Umaru (African Journal of Biochemistry and Molecular Biology Research, 2026)
Exposure to petroleum hydrocarbons such as Bonny Light crude oil (BLCO) is associated with oxidative stress and organ toxicity, particularly renal damage. Chrysophyllum albidum is a medicinal plant rich in antioxidant phytochemicals, yet its protective role against crude-oil-induced renal oxidative injury remains insufficiently explored. This study evaluated the effect of ethanol extract of C. albidum stem bark on renal antioxidant enzyme activity and lipid peroxidation in Wistar rats exposed to BLCO. Wistar rats were assigned to control, BLCO-only, and BLCO plus C. albidum extract treatment groups. Renal tissues were analyzed for catalase, superoxide dismutase, and glutathione peroxidase activities, as well as malondialdehyde levels as a marker of lipid peroxidation. The findings showed that BLCO exposure significantly reduced catalase, superoxide dismutase, and glutathione peroxidase activities and markedly increased malondialdehyde levels compared with the control group, p < .05. Treatment with C. albidum extract produced a dose-dependent increase in antioxidant enzyme activities and significantly reduced malondialdehyde levels relative to the BLCO-only group, p < .05, indicating attenuation of renal oxidative stress. The study concludes that ethanol extract of C. albidum stem bark exhibits antioxidant and nephroprotective effects against BLCO-induced renal oxidative damage. These findings contribute to toxicological and phytomedicinal research by highlighting the potential of C. albidum to enhance endogenous antioxidant defenses and suppress lipid peroxidation in crude-oil-related kidney toxicity.